2021
DOI: 10.3389/fphar.2021.609693
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Attenuates Cerebral Ischemia-Reperfusion Injury Induced Neuronal Apoptosis by Down-Regulating the CNPY2 Signaling Pathway

Abstract: Berberine (BBR) has a neuroprotective effect against ischemic stroke, but its specific protective mechanism has not been clearly elaborated. This study explored the effect of BBR on the canopy FGF signaling regulator 2 (CNPY2) signaling pathway in the ischemic penumbra of rats. The model of cerebral ischemia-reperfusion injury (CIRI) was established by the thread embolization method, and BBR was gastrically perfused for 48 h or 24 h before operation and 6 h after operation. The rats were randomly divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…Berberine not only contributes to cancer therapy but also has reported benefits in the treatment of inflammation, diabetes, and pathogenic infection and can attenuate acute renal injury and neurodegenerative diseases [34][35][36][37][38][39]. We synthesized B4 and B5 from berberrubine, derived from berberine; both B4 and B5 exert higher anti-NSCLC activities than berberine and berberrubine.…”
Section: Discussionmentioning
confidence: 99%
“…Berberine not only contributes to cancer therapy but also has reported benefits in the treatment of inflammation, diabetes, and pathogenic infection and can attenuate acute renal injury and neurodegenerative diseases [34][35][36][37][38][39]. We synthesized B4 and B5 from berberrubine, derived from berberine; both B4 and B5 exert higher anti-NSCLC activities than berberine and berberrubine.…”
Section: Discussionmentioning
confidence: 99%
“…During ERS, the binding partner of CNPY2 changes from GRP78 to PERK, resulting in activation of the PERK-CHOP pathway and promotion of apoptosis ( Urra and Hetz, 2017 ). Inhibition of the CNPY2 signaling pathway can block neuronal apoptosis induced by CIRI, leading to neuroprotection ( Zhao et al, 2021 ). In addition, a study showed that the transcription of CHOP is regulated by ATF6 ( Yoshida et al, 2000 ).…”
Section: Endoplasmic Reticulum Stress and Cell Apoptosismentioning
confidence: 99%
“…Berberine (BBR, ( Figure 7C ) natural isoquinoline alkaloid, is a major compound isolated from the Chinese herb Coptis chinensis Franch. ( Wang et al, 2021d ), and studies have found that BBR has pharmacological activities against cancer, hypolipidemic, cardiovascular, anti-inflammatory, and antioxidant stress ( Zhao et al, 2021 ). Wei et al studied the potential medicinal value of berberine in vitiligo.…”
Section: Other Compoundsmentioning
confidence: 99%